AI and Confidentiality protection in International Commercial Arbitration: Analysis of the existing legal framework - Mark-Silas A. Malekela (Discover Artificial Intelligence)
Abstract The use of Generative Artificial Intelligence (AI) tools in international commercial arbitration reveals a complex intersection with the potential risk of confidential data breaches. Adopting a doctrinal research approach, this research article analyses the legal and regulatory framework applicable to ensure responsible and ethical uses of AI so as to protect confidentiality in international arbitration. This article argues that the use of AI in international arbitration has brought in a new age of efficiency and accuracy in international arbitration, but it also raises concerns on the protection of confidentiality as third-party owned AI tools and systems are prone to a potential risk of confidential data breaches and confidentiality violations on volumes of data stored together in AI tools. The application of the guidelines and principles on the use of AI in international arbitration as well as emerging regulations and laws on AI have varied approaches that are either discretionary or only play a guiding role on the protection of confidential information in international arbitration. Ultimately, this article recommends that it is imperative for the upcoming versions of institutional arbitration rules to enhance the confidentiality obligations in arbitration proceedings with a focus on the integration of AI tools. Alternatively, with the use of confidentiality orders, arbitration participants must ensure that appropriate safeguards are in place to ensure that confidentiality is a core consideration from the initial stages of deploying AI tools. Confidentiality by design could also be applied in Generative AIs used by law firms, arbitral tribunals or institutions.